6+2x=4(x+3)

Simple and best practice solution for 6+2x=4(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2x=4(x+3) equation:


Simplifying
6 + 2x = 4(x + 3)

Reorder the terms:
6 + 2x = 4(3 + x)
6 + 2x = (3 * 4 + x * 4)
6 + 2x = (12 + 4x)

Solving
6 + 2x = 12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6 + 2x + -4x = 12 + 4x + -4x

Combine like terms: 2x + -4x = -2x
6 + -2x = 12 + 4x + -4x

Combine like terms: 4x + -4x = 0
6 + -2x = 12 + 0
6 + -2x = 12

Add '-6' to each side of the equation.
6 + -6 + -2x = 12 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = 12 + -6
-2x = 12 + -6

Combine like terms: 12 + -6 = 6
-2x = 6

Divide each side by '-2'.
x = -3

Simplifying
x = -3

See similar equations:

| 4n+2=-4n+-2 | | 3x^2-28x-20=0 | | 2t+x=19 | | s=t+4 | | 36c^2-84cd+49d^2= | | (2x-10)(x+2)=0 | | 12x+12=72 | | 4x+100=22 | | 7z-2=6x+25 | | 3+x+4+5=10+6x+5-2x | | 7-2x=4x-5 | | 8+4x=20+8x | | 4x^2+24x-448=0 | | [2x-3]=9 | | 3n+3(-n+3)=3 | | -12x+16=-12x+-16 | | 8y=40+3y | | 2(6x-2x)=56 | | 2x^5+4x^4-4x^3-8x^2=0 | | 8x=3(5+x) | | -6x+-3=-6x-2 | | 5z^2+10z=0 | | 6x+20=x+50 | | 12-20=15p+15 | | 9(8y-5)-7(6y+7)=20y | | 3b-3(b-1)=2(3b-1)+6 | | n^2-4n+5=0 | | 4x^2-8x=-3 | | 8(2x+10)-6x=110 | | 8(2x+10)-6x=110 | | 3x-4y+26=0 | | 2j-0.75=1j |

Equations solver categories